Platform for in-plane ZT measurement and Hall coefficient determination of thin films in a temperature range from 120 K up to 450 K. Issue 20 (27th October 2016) - Linseis, Vincent; Völklein, Friedemann; Reith, Heiko; Woias, Peter; Nielsch, Kornelius
Abstract: Abstract : The characterization of nanostructured samples with at least one restricted dimension like thin films or nanowires is challenging but important to understand their structure and transport mechanism and to improve current industrial products and production processes. We report on the development of a chip-based platform to simultaneously measure the in-plane electrical and thermal conductivity, the Seebeck coefficient as well as the Hall constant of a thin film in the temperature range from 120 K up to 450 K and in a magnetic field of up to 1 T. Due to the design of the setup, time consuming preparation steps can be omitted and a nearly simultaneous measurement of the sample properties is achieved. Typical errors caused by different sample compositions, varying sample geometries, and different heat profiles are avoided with the presented measurement method. As a showcase study displaying the validity and accuracy of our system, we present measurements of the thermoelectric properties of a 110 nm Bi87 Sb13 thin film in the temperature range from 120 K up to 450 K.